Pengelolaan Air pada Budidaya Tanaman Padi (Oryza sativa L.) Pasang Surut Di Desa Sanglar Kecamatan Reteh Kabupaten Indragiri Hilir - Adi Wibowo; Ardian Ardian; Idwar Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The aim of this study is to determine the way in which water management and rice cultivation techniques are carried out in tidal land. This study uses a survey method and interviews with rice farmers in Sanglar Village, Reteh Regency, Indragiri Hilir Regency. Farmers 'respondents were collected by means of targeted sampling based on the location of farmers' groups downstream, in the middle and upstream of the secondary channel. Each part of upstream, middle and downstream will be taken 2 farmer groups as samples then 8 farmers will be taken as survey respondents. So thatthe total respondents were 48 tidal rice farmers. The results of the research data are presented in the form of tables and images that are described descriptively. The management of water used in Sanglar Village is classified as simple water management, characterized by the condition of buildings that are still made of earth and there are no building meters and retention. The cultivation technique used in Sanglar Village is one of the traditional cultivation techniques. This can be seen from planting to harvesting, most farmers have not used Alsintan and agricultural innovations. The highest productivity is indicated by the downstream channel with 3.73 tons. Ha-1 is still relatively low due to simple water management and traditional breeding techniques that require improvement in water management and cultivation techniques.Keyword : Water Management, Rice Cultivation, Tidal Land